Meningkatkan Motivasi Belajar Siswa Kelas V SDI Kletek Menggunakan Model Pembelajaran Inkuiri - Fridolin Rikyano Lalu (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This research aims to increase the learning motivation of grade V students of SDI Kletek through the application of the Inquiry learning model in the subject of Pancasila Education. The low motivation of students to learn can be seen from the lack of participation in learning, the low activity of asking questions, and the minimum responsibility in completing tasks. The research uses the Classroom Action Research (PTK) approach with the Kemmis and McTaggart models which is carried out in three cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The research subjects amounted to 12 students in class V of SDI Kletek. Data collection techniques include observation, questionnaire, and documentation, while data analysis is carried out descriptively, quantitatively, and qualitatively. The results of the study show that the application of the Inquiry learning model is able to increase students' learning motivation in each cycle. Increased motivation can be seen from increased curiosity, activeness in discussions, courage to express opinions, and students' responsibilities during the learning process. The results of the study showed that the indicators of research success were achieved after the implementation of the action in cycle III. Thus, the Inquiry learning model is effectively used to increase students' learning motivation in the subject of Pancasila Education in grade V of SDI Kletek.